The effects of foreign direct investment on youth unemployment in the Southern African Development Community - Mkombe, D.; Hirpa Tufa, A.; Alene, A.; Manda, J.; Feleke, S.; Abdoulaye, Tahirou; Manyong, Victor (Informa UK Limited, 2020)
This paper examines the effect of foreign direct investment (FDI) on youth unemployment in the Southern African Development Community (SADC) region using panel data from the World Bank World Development Indicators for the period 1994–2017. Results from the Feasible Generalized Least Squares (FGLS-Parks) technique show that FDI has an insignificant effect on reducing youth unemployment in the SADC region. This could be because the type of FDI in the region is partly mergers and acquisitions, which has fewer jobs creating capacity compared to Greenfield investment. This suggests the need for governments in the region to pursue labour-absorbing FDI policies and also ensure that foreign investment inflows are channelled towards labour-intensive sectors that have high labour absorptive capacity such as horticulture and floriculture.